2019
DOI: 10.1017/s136898001900301x
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality is associated with reduced risk of hypertension among Inner Mongolia adults in northern China

Abstract: Objective:The present study investigated the association between dietary patterns and hypertension applying the Chinese Dietary Balance Index-07 (DBI-07).Design:A cross-sectional study on adult nutrition and chronic disease in Inner Mongolia. Dietary data were collected using 24 h recall over three consecutive days and weighing method. Dietary patterns were identified using principal components analysis. Generalized linear models and multivariate logistic regression models were used to examine the associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Located in northern China, Inner Mongolia has different food culture from other regions. Although the consumption of fresh vegetables and fruit has increased in recent years, the diet of local residents was intake meat and animal fat as the main component [21]. A recent cohort study revealed that higher fat intake was related to a greater risk of obesity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Located in northern China, Inner Mongolia has different food culture from other regions. Although the consumption of fresh vegetables and fruit has increased in recent years, the diet of local residents was intake meat and animal fat as the main component [21]. A recent cohort study revealed that higher fat intake was related to a greater risk of obesity [22].…”
Section: Discussionmentioning
confidence: 99%
“…The health belief model (HBM) holds that individual behavior is the external manifestation of psychological activities and the adoption of healthy behaviors is related to individuals' perceived behavioral benefits and barriers [4]. Previous studies have reported significant association between attitudes towards healthy eating and diet quality, as well as the association between higher diet quality and lower incidence of hypertension and other diseases [22][23][24]. Therefore, it is necessary to guide and direct Chinese residents to develop healthy diet-related attitudes, so as to lay a good foundation for the adoption of healthy eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Inner Mongolia is inland region, located in northwest China, and the population has dietary cultures and ethnic characteristics that differ from the rest of China. People in Inner Mongolia consume less vegetables and fruits, and more meat, oil and salt [12]. Inner Mongolia consists mainly of Han and Mongolian.…”
Section: Introductionmentioning
confidence: 99%